Acehnese Creative Dance as an Intervention for Problematic Digital Use in Elementary Schools - Putry Julia; Faisal Anwar (Gondang: Jurnal Seni dan Budaya, 2025)
Excessive use of digital devices among elementary school students in Indonesia has become increasingly concerning as it may lead to digital problematic digital use with negative impacts on cognitive, social, and emotional development. This study aimed to evaluate the effectiveness of Acehnese creative dance intervention in reducing digital problematic digital use among elementary school students. The research employed a quasi-experimental method with a One Group Pretest–Posttest Design. The sample consisted of 45 students from five elementary schools in Banda Aceh selected through purposive sampling. Data were collected using a modified questionnaire by Ratuaki (2023) measuring six dimensions of digital problematic digital use. The intervention was conducted over two weeks with seven sessions. The paired sample t-test indicated a significant increase in mean scores from pre-test (M = 44.82) to post-test (M = 63.56), Since higher scores indicate lower levels of digital problematic digital use due to reverse scoring applied to all negative problematic digital use indicators, this result demonstrates a significant reduction in students’ digital problematic digital use levels following the intervention with a size (Cohen’s d = 0.780). Furthermore, ANOVA results revealed no significant differences across schools (p = 0.564). These findings confirm that Acehnese creative dance is effective in reducing students’ dependency on digital devices while simultaneously preserving local cultural heritage. The study recommends integrating traditional dance into school curricula as a local wisdom-based digital detox strategy. Beyond its educational relevance, the intervention also demonstrates how cultural practices can be recontextualized to address contemporary challenges faced by younger generations, thus offering insights for educators, policymakers, and future researchers interested in sustainable approaches to digital well-being.